Hull Structural Scantlings of the Golden Series Otoryacht - Patek, Peter (Communications - Scientific letters of the University of Zilina, 2001)
The paper describes the procedures for scantlings of some hull structural elements from FRP materials. The solution and software are based on the rules of classification societies GL-BV-RINA. It allows to estimate the optimal skin-plating thickness and other dimensions of the stiffeners. These procedures are applied for design of the large high-speed craft Golden Series designed for the open-sea class. The luxurious yachts built in Bratislava shipyard for foreign customer.